The Presence of Silica Bodies in the Foliar Epidermis of Zoysiagrass. Issue 1 (19th October 2017) - Ushilo, Masakazu J.; Naganuma, Kazuo; Matsuda, Yasushi; Uchida, Masaya; Klittich, Daniel S.
Abstract : The presence of silica bodies (SBs) in the foliar epidermis of zoysiagrass ( Zoysia spp. Willd.) is a special characteristic, the function of which is not well understood. To quantify the importance of SB, we evaluated foliar SB densities and sizes of five Zoysia species [ Z. japonica Steud., Z. matrella (L.) Merr., Z. pacifica (Goudsw.) M. Hotta & S. Kuroki, Z. minima (Colenso) Zotov, and Z. macrostachya Franch. & Sav.] including three ecotypes of each species using tabletop scanning electron microscopy. Our results demonstrated that abaxial SB density was significantly higher (mean: 734.3 mm −2 ) than that of adaxial SB (mean: 317.7mm −2 ) in all species. Abaxial SB size was also significantly larger (mean: 80.0 μm 2 ) than that of the adaxial SB (mean: 61.4 μm 2 ) in all species. Zoysia japonica had significantly higher SB density and size than the other tested Zoysia spp. Location‐specific sizes of foliar abaxial SB were identified: large on the midrib, medium on other ribs, and small in the costal zone. These results support the hypothesis that foliar SBs of zoysiagrass function to protect rib bundles and Kranz anatomy from physical damages, and to assist light absorbance for C4 photosynthesis through inhibiting leaves from twisting. Further work assessing SB impact on growth efficiency, survival strategy, and the utility of zoysiagrass is needed.